2018
DOI: 10.3389/fonc.2018.00174
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid Metabolism: A Key Player in Breast Cancer Metastasis Revealed by Metabolomics

Abstract: Metastatic breast cancer is currently incurable. It has recently emerged that different metabolic pathways support metastatic breast cancer. To further uncover metabolic pathways enabling breast cancer metastasis, we investigated metabolic differences in mouse tumors of differing metastatic propensities using mass spectrometry-based metabolomics. We found that sialic acid metabolism is upregulated in highly metastatic breast tumors. Knocking out a key gene in sialic acid metabolism, Cmas, inhibits synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 74 publications
3
60
2
Order By: Relevance
“…So far, our results indicate that loss of sialic acids might actually be detrimental in CRC and thereby contradict other studies investigating the role of tumor sialylation on the anti‐tumor immune response . To translate our findings to human CRC patients, we analyzed CMAS gene expression in a human colorectal cancer cohort (GSE39582) in relation to disease progression and survival.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…So far, our results indicate that loss of sialic acids might actually be detrimental in CRC and thereby contradict other studies investigating the role of tumor sialylation on the anti‐tumor immune response . To translate our findings to human CRC patients, we analyzed CMAS gene expression in a human colorectal cancer cohort (GSE39582) in relation to disease progression and survival.…”
Section: Resultscontrasting
confidence: 62%
“…The different mouse strains, with their different predisposition toward T helper 2 (Th2) and Th1 responses, as well as the different tumor model used, may have impacted the outcome of the respective studies. Discrepancies due to tumor type‐specific effects is further supported by the cohort data presented in both studies (Fig. a ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Generally, tumor cells increase the uptake of glucose, the raw material for sialic acid synthesis. It was reported that sialic acid metabolism was upregulated in highly metastatic breast tumors, while knocking out CMAS gene, a key node in sialic acid metabolism, inhibited the synthesis of the activated form of sialic acid and decreased the formation of lung metastases in vivo [32]. On the other hand, the aberrant expression of sialyltransferases and sialidases accelerated and sustained sialylation status on glycoconjugates.…”
Section: Functions Of Sialic Acids In Tumor Biologymentioning
confidence: 99%
“…CMAS, which is in the sialic acid pathway, has a key role in breast cancer and is significantly associated with decreased breast cancer patient survival. Also, low CMAS gene expression is correlated with reduced recurrencefree survival in a human colorectal cancer cohort [27,28]. XCL2 expression increases with the degree of malignancy of lung cancer, indicating that it could be an important target in gene therapy for lung cancer [29].…”
Section: Discussionmentioning
confidence: 98%